The Manager's Guide to HR - Muller, Max (Ascent Audio, 2018)
Extensively revised, the second edition of The Manager's Guide to HR covers all the key areas and brings readers up to speed on current developments in employment law, including: - How social media is changing the recruitment landscape - Shifting labor standards regarding compensation and benefits - The National Labor Relations Board's stance on work-related employee speech on social media - The Employee Retirement Income Security Act - New record-keeping requirements - Amendments to the Family and Medical Leave Act and the Americans with Disabilities Act - And more Featuring step-by-step guidance on everything from COBRA compliance to privacy issues, this trusted resource is now-once again-the most up to date.